M*A*S*H. Season ten [videorecording (DVD)] - Gelbart, Larry; Metcalfe, Burt; Dubin, Charles; Alda, Alan, 1936-; Farrell, Mike; Morgan, Harry, 1915-2011; Swit, Loretta; Stiers, David Ogden; Farr, Jamie, 1934-; Christopher, William, 1932-2016 (Twentieth Century Fox Home Entertainment, 2006)
Explores the day-to-day lives of the people who live and work at the Mobile Army Surgical Hospital (MASH) stationed three miles from the front during the Korean War.